Psychosomatic symptoms in patients with alopecia areata and vitiligo - Kökçam, İbrahim; Akyar, Nevzat; Saral, Yunus; Oğuzhanoğlu, Nalan K. (My University, 1999)
Vitiligo and alopecia areata present an excellent opportunity to f ocus on the effect of impaired appearance on the lives of the persons with these diseases. Emotional stress has precipitated vitiligo and alopecia areata in some patients. Twenty-eight patients suffering from alopecia areata and vitiligo and twenty healthy persons at ages between ten and sixty underwent psychological tests of examination with special regard to verification of their psychiatric symptoms. The results were compared for all groups. The results revealed that depressive symptomatology in patients with vitiligo and alopecia areata was higher than in the control group (respectively, 55%, 36%, 15%). As a result, we conclude that the cosmetic disfigurement may be of great importance on the lives of persons with these diseases.
Keywords: Vitiligo; Psychophysiologic Disorders; Alopecia Areata